Power and progress our thousand-year struggle over technology and prosperity - Acemoglu, Daron; Johnson, Simon 1963- (New York PublicAffairs, 2023)
"Two bestselling authors overturn conventional wisdom about how economies work, revealing the untold story of who wins and who loses the rewards of prosperity, in a work that fundamentally transforms how we look at and understand the world"--
Contents: Control over technology - - Canal vision - - Power to persuade - - Cultivating misery - - A middling sort of revolution - - Casualties of progress - - The contested path - - Digital damage - - Artificial struggle - - Democracy breaks - - Redirecting technology.
Includes bibliographical references (pages 475-516) and index.
Keywords: Progress; Technology -- Economic aspects; Technology -- Social aspects